MINERALOGICAL STUDY OF SUPERGENE PORPHYRY COPPER ORES FROM SUNGAI MAK PROSPECT IN GORONTALO AND THE EFFECTIVENESS OF THE ORE EXTRACTION BY HEAP LEACHING - Kharis Prasetya Adhi, Alandika
Previous studies indicated that copper ore in the Sungai Mak Block, Gorontalo is a supergene porphyry type. One of the options for processing of the secondary copper sulfide ore (supergene ore) is through sulfuric acid leaching followed by solvent extraction and electrowinning. The leaching methods that can be done are agitation leaching and heap leaching, which are both use oxidizing agents to oxidize sulfur in copper sulfide mineral. In this research, studies of ore mineralogical characteristic, acid leaching behavior with coarse bottle roll and column test as well as percolation testing were performed to determine the characteristics of the ore from the Gorontalo Mak River Sungai Mak, Gorontalo and to investigate the effectiveness of the copper extraction from this ore by heap leaching method. The experimental work started with the ore preparation that includes crushing, grinding, sampling, and sieving, followed by the characterization of the dominant mineral in the ore sample using X-Ray Diffraction (XRD), chemical composition analysis by X-Ray Fluorescence (XRF) and Inductively Coupled Plasma (ICP), mineragraphy analysis of the polished ore section. Coarse bottle roll leaching tests were carried out for 168 hours under variations of ore particle size distribution, sulfuric acid concentration, and clay content in the ore to determine their effects on copper extraction. Percolation tests which include slump test and flowrate test—refers to the Kappes Percolation Test method—were conducted to evaluate the characteristic of the agglomerates before column leaching test was done. Column leaching tests were carried out in flexy glass column for 60 days by varying the effects of pre-washing, the effects of agglomeration, and the effect of sulfuric acid concentration. Dissolved Cu and Fe concentration as a function of time were measured by Atomic Absorption Spectrophotometer (AAS). XRD, XRF, and mineragraphy analysis results show that the ore from Sungai Mak Gorontalo is a secondary copper sulfide ore with high clay content. Results of the coarse bottle roll leaching tests show that the finer ore fraction size, the higher sulfuric acid concentration, and the lower clay content in the ore tend to result in higher copper extraction percentages. It was found from the results of percolation tests that pre-washing and agglomeration of the ore samples are needed to promote a good percolation of the leaching test through the ore heap. The agglomeration of the washed ore enhances the Cu extraction from 41.18% to 60,26% after 60 days of column test. Results of the overall testworks indicated that heap leaching method can be utilized for copper extraction from Sungai Mak ore.